Trends and Factors Associated With Peripheral Vascular Interventions for the Treatment of Claudication From 2011 to 2022: A National Medicare Cohort Study - Chen Dun; David P. Stonko; Sanuja Bose; Alana C. Keegan; Katherine M. McDermott; Kranti C. Rumalla; James H. Black; Corey A. Kalbaugh; Martin A. Makary; Caitlin W. Hicks (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Previous cross‐sectional studies have identified wide practice pattern variations in the use of peripheral vascular interventions (PVIs) for the treatment of claudication. However, there are limited data on longitudinal practice patterns. We aimed to describe the temporal trends and charges associated with PVI use for claudication over the past 12 years in the United States. Methods and Results We conducted a retrospective analysis using 100% Medicare fee‐for‐service claims data to identify all patients who underwent a PVI for claudication between January 2011 and December 2022. We evaluated the trends in utilization and Medicare‐allowed charges of PVI according to anatomic level, procedure type, and intervention settings using generalized linear models. Multinomial logistic regressions were used to evaluate factors associated with different levels and types of PVI. We identified 599 197 PVIs performed for claudication. The proportional use of tibial PVI increased 1.0% per year, and atherectomy increased by 1.6% per year over the study period. The proportion of PVIs performed in ambulatory surgical centers/office‐based laboratories grew at 4% per year from 12.4% in 2011 to 55.7% in 2022. Total Medicare‐allowed charges increased by $11 980 035 USD/year. Multinomial logistic regression identified significant associations between race and ethnicity and treatment setting with use of both atherectomy and tibial PVI. Conclusions The use of tibial PVI and atherectomy for the treatment of claudication has increased dramatically in in ambulatory surgical center/office‐based laboratory settings, non‐White patients, and resulting in a significant increase in health care charges. There is a critical need to improve the delivery of value‐based care for the treatment of claudication.